2022
DOI: 10.3390/su142416955
|View full text |Cite
|
Sign up to set email alerts
|

The Safe Development Paradox in Flood Risk Management: A Critical Review

Abstract: Climate change and continued urban development in flood-prone areas exacerbate flood risks. Flood Risk Management authorities often turn to structural protection measures to minimise losses. However, these measures often lead to infrastructural lock-ins with potential unintended consequences as increased safety can induce increased development, ultimately leading to higher losses in the event of failures of the structural safe-guards in place. This process has been referred to as the Safe Development Paradox: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
2
3
0
1
Order By: Relevance
“…However, disaster mitigation targeting landslides and multi-hazards can also trigger the SDP and LE. Also, similar to other reviews, we found that a key limitation in SDP and LE research is its narrow geographical focus, particularly the underrepresentation of the Global South (Breen et al 2022).…”
Section: Discussion and Recommendations For Further Researchsupporting
confidence: 88%
See 3 more Smart Citations
“…However, disaster mitigation targeting landslides and multi-hazards can also trigger the SDP and LE. Also, similar to other reviews, we found that a key limitation in SDP and LE research is its narrow geographical focus, particularly the underrepresentation of the Global South (Breen et al 2022).…”
Section: Discussion and Recommendations For Further Researchsupporting
confidence: 88%
“…3), with the majority based in USA (n = 12), followed by Italy (n = 5) and Australia (n = 4). This distribution highlights the disparity in research focus between the Global North (n = 32) and the Global South (n = 9), a pattern also observed in previous literature reviews (Vanelli et al 2021;Fischer et al 2021;Breen et al 2022).…”
Section: Spatio-temporal Scope Of the Reviewed Articlessupporting
confidence: 70%
See 2 more Smart Citations
“…La mala adaptación puede producirse, por ejemplo, si las infraestructuras de ingeniería (p. ej., diques) o los programas de respuesta ante desastres crean una falsa sensación de seguridad que incentiva el desarrollo continuo en zonas peligrosas, lo que a su vez produce mayores pérdidas en caso de falla del sistema, una situación conocida como la paradoja del desarrollo seguro 101,102,103 . La adaptación ajustada a un contexto específico puede volverse mala adaptación si se ve sometida a un tipo de peligro o contexto diferente, como cuando los espacios abarrotados de los refugios comunitarios o los centros para refrescarse contribuyen a la propagación de enfermedades 104,105 .…”
Section: Acciones De Adaptación Definidas Por Múltiples Factoresunclassified